132 Non-synonymous SMAD6 mutations impaired inhibition of bmp signalling in patients with congenital cardiovascular malformation. (9th June 2011) - Tan, H L; Glen, E A; Topf, A L; Hall, D H; O'Sullivan, J J; Sneddon, L; Wren, C; Avery, P; Lewis, R J; ten Dijke, P; Arthur, H M; Goodship, J A; et al.
Abstract : Introduction: Congenital cardiovascular malformation (CVM) exhibits familial predisposition but the specific genetic factors involved are unknown. Bone morphogenetic proteins (BMPs) regulate many processes during development, including cardiac development. Five genes of the BMP signalling were surveyed for novel variants predisposing to CVM risk. One of the genes, SMAD6, functions as an inhibitory SMAD which preferentially inhibits BMP signalling. The SMAD6 knockout mouse is characterised by cardiac valve and outflow tract defects, including aortic ossification. We hypothesised that rare functional variation in SMAD6 could predispose to congenital cardiovascular malformation (CVM). Methods: The coding regions of BMP2, BMP4, BMPR1A, BMPR2 and SMAD6 were sequenced in 90 unrelated Caucasian cases of CVM. The MH2 domain of SMAD6 were further sequenced in additional 346 CVM patients. Functional effects of the wild-type and variant SMAD6 proteins were expressed in C2C12 cells and their capacity to inhibit ALK3 activated expression of a BMP-responsive reporter, or to inhibit osteogenic differentiation (using an alkaline phosphatase assay) was assessed. Results: We identified two novel non-synonymous variants, P415L and C484F, that were not present in 1000 ethnically-matched controls. P415L was identified in a patient with congenital aortic stenosis and C484F was identified in a patient with coarctation and calcification of the aorta. Both mutations are in evolutionarily conserved amino acid residues and are predicted to be damaging by in silico analysis. This was confirmed in functional assays as both SMAD6 variants failed to inhibit BMP signalling compared with wild-type SMAD6. The P415L mutant appeared to be hypomorphic whereas C484F appeared to be a null allele in the luciferase assay. The C484F mutant had a significantly (p<0.05) lower capacity to inhibit alkaline phosphatase generation in response to BMP signalling. Conclusions: This is the first time that functional mutations in SMAD6 have been described in patients with CVM, specifically those with calcific aortic malformations. Our data suggest that inadequate inhibition of BMP signalling pathway due to genetic variation in SMAD6 may be an important factor in CVM.